2021
DOI: 10.1016/j.eprac.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Ultra Rapid-Acting Inhaled Insulin Improves Glucose Control in Patients With Type 2 Diabetes Mellitus

Abstract: Objective: To determine whether the use of an inhaled insulin would improve HbA1c. Methods: This study was performed in 20 type 2 diabetes mellitus (T2DM) participants with HbA1c values !7.5 (58) to 11.5% (102 mmol/mol) on a variety of glucose-lowering regimens. Prandial Technosphere insulin (TI) was rapidly titrated based on a treatment algorithm using postprandial blood glucose to calculate premeal doses. A 2-week baseline period was followed by 12 weeks of active treatment with TI. The primary outcome was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Diabetes mellitus is a metabolic disease caused by defective secretion and utilization of insulin and characterized by hyperglycemia resulting from multiple causes. α‐amylase in human pancreatic cells helps control the breakdown of starch in the body, thus preventing postprandial hyperglycemia (Levin et al, 2021). Early studies have revealed that Aloe vera can lower the levels of blood sugar and blood lipids in mouse models of non‐insulin‐dependent diabetes (Kim et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus is a metabolic disease caused by defective secretion and utilization of insulin and characterized by hyperglycemia resulting from multiple causes. α‐amylase in human pancreatic cells helps control the breakdown of starch in the body, thus preventing postprandial hyperglycemia (Levin et al, 2021). Early studies have revealed that Aloe vera can lower the levels of blood sugar and blood lipids in mouse models of non‐insulin‐dependent diabetes (Kim et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…HbA1c has been a common indicator used to evaluate patients’ blood glucose control in recent months. The more obvious the increase in HbA1c level, the worse the blood glucose control[ 13 , 14 ]. However, excessive blood glucose levels can damage vascular endothelial cells in patients with DN and easily induce spasms of renal afferent arterioles, thus causing damage to the renal units due to ischemia and hypoxia[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…where, t is the total dose administered to the patient [49]. Fluid replacement is performed in patients with blood glucose greater than 400 mg/dl, dehydration, and ketosis.…”
Section: Isf =1800/tmentioning
confidence: 99%